COVID-19 Pandemic and its Impact on Vaccine Hesitancy: A Review - Suci A. Widyaningsih; Mohamad S. Hakim (Oman Medical Journal)
Vaccination is one of the most successful public health initiatives in human history, significantly reducing the incidence and severity of infectious diseases. The success of any vaccination program depends on several factors, including effective leadership, funding, distribution management, and addressing vaccine hesitancy. Vaccine hesitancy, the delay or refusal to be vaccinated despite the availability of immunization services, has always been prevalent in societies but has become more pronounced during the COVID-19 pandemic. During the pandemic, anti-vaccine activists persistently promoted and increased vaccine hesitancy by using social media to spread rumors, propaganda, and conspiracy theories. The rising vaccine hesitancy among the public became a major challenge to the success of the COVID-19 immunization program. There are also indications that this hesitancy may have generalized against more traditional vaccines. This literature review explores the structure and evolving dynamics of COVID-19 vaccine hesitancy and the resultant generalized skepticism towards other vaccinations. It also suggests future strategies to address and mitigate the phenomenon of vaccine hesitancy.